From mechanism to therapy: the journey of CD24 in cancer - Zhao, Kai; Wu, Caifeng; Li, Xiangjun; Niu, Mengchao; Wu, Dan; Cui, Xiaofeng; Zhao, Hai (Frontiers in Immunology, 2024)
CD24 is a glycosylphosphatidylinositol-anchored protein that is expressed in a wide range of tissues and cell types. It is involved in a variety of physiological and pathological processes, including cell adhesion, migration, differentiation, and apoptosis. Additionally, CD24 has been studied extensively in the context of cancer,where it has been found to play a role in tumor growth, invasion, and metastasis. In recent years, there has been growing interest in CD24 as a potential therapeutic target for cancer treatment. This review summarizes the current knowledge of CD24, including its structure, function, and its role in cancer. Finally, we provide insights into potential clinical application of CD24 and discuss possible approaches for the development of targeted cancer therapies.